Papilledema in Space Flight: Pathogenesis, Diagnostics and Monitoring - I. A. Makarov; S. N. Danilichev (Oftalʹmologiâ, 2020)
Some Russian cosmonauts in space flight have revealed swelling of the optic nerve head of varying severity. Four clinical cases presented in this article. A quantitative method for the analysis of OCT images of the optic nerve head and the retina has been developed for the diagnosis and monitoring of the optic nerve’s state. This method is quite informative, regardless of the opinion of each specific medical consultant; diagnosis of optic nerve head edema can be performed according to the generally accepted Frisen’s grading, and thus objectify its diagnostic capabilities. In cases when changes in the optic nerve head are not visualized during ophthalmoscopy, quantitative analysis of OCT images allows one to quantify the presence of optic nerve head edema at the subclinical stage. This objective diagnostic method allows us to establish and quantify the amount of industrial activity, which, with edema of the optic nerve because of intracranial hypertension, mostly pronounced on the nasal side of the nerve disc. Determining the thickness of the retina and head of the optic nerve in the nasal side are paramount for monitoring changes in papilledema in dynamics, especially in the subclinical and 0 stage according to Frisen. Quantitative measurements of the optic nerve head in the temporal side are necessary for the diagnosis, developed papilledema and differential diagnosis of 1-2 stages on the Frisen scale. The use of this diagnostic method has the great importance in assessing the influence of various factors of the space flight on the optic nerve head.